Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2023)
Table of Content: 1. Indicators of Desertification and its Impact on the Degradation of Agricultural Lands: A study of the Geography of Gadaref State Dr. Salwa Hassan Ahmed Sulieman 2. Estimating an almost ideal demand system for red meat consumption in Libya Throughout the Year 2021 (A Case Study of the Municipality of Hay Al-Andalus) Mrs. Najat Mustafa Aljazeri, Prof. Said Yousif Khairi, Prof. Ragab Emhemed Alwerfelli 3. Impact of Cookware Types on Leaking Heavy Metals into Food based on pH Values, and their Potential Impact on the Health Status of a Saudi Sample using a Survey Study Design Dr. Waheeba Ahmed Al-Faki, Ruya Mohammed Al-Shabrami, Mudhi Abdullah Aba Al-Khail1, Hala Abdul-Aziz Al-Muzaini, Aroob Ahmed Al-Ghafis, Safyah Ahmed Al-Adl, Aljouharah Khaled Al-Aqeel, Mashael Ali Al-Batah 4. Biological Control of Lesser Date Moth (Batrachedra. Amydraula/ mayrick) using the local parasitoid Goniozus omanensis Mrs. Samia Juma Suliman Al-Naabi, Mrs. Najma Mahmood Somar Al-Zadgali, Dr. Rashid Saif Al-Shidi 5. Effect of crossbreeding on some productive characteristics of laying hens Lecturer Esraa Mobsher Tawfeq, Asst-Lecturer Haytham Mohammed Sabeeh, Asst-Lecturer Omar AbdulHameed Al-Kurjia 6. Chemical, Bioactive and antioxidant properties of Alhydwan (Boerhavia elegana Choisy) Seeds- A review Mrs. Afnan Othman Mohammed Albisher, Dr. Asmahan Azhari Ali Mohammed, Prof. Sahar H. S. Mohamed